ENERWAT project: some preliminary results - Matos, C. (2018)
Water and energy are two linked important resources and its use efficient must be profoundly studied. On the other hand, it is believed that there are significant differences between the pattern of water and energy consumption in rural and urban areas, whose influencing factors require study too. Swveral research state a large difference in urban and rural household water consumption pattern. However, rural household's consumptions are under-researched compared to urban residential consumptions. This paper aims to provide some preliminary results of a research project named ENERWAT, supported by the Portuguese Science and Technology Fiundation. One of the parts of the referred project was the design, application and results analysis of a survey, in order to find the main differences in the water and energy consumptions at the end-use level, and tha factores that influence it in urban and rural households. A total of 245 households participated in the research during the year of 2016 (urban: 110 dwellings) and (rural: 135 dwellings), responding to questions such as their family composition, dwellings characterization, water and energy consumption habits and conservation behaviors of these resources. Some of the obtained results will be here provided.